Chronic traumatic wound. A case report - Szewczyk, Maria T.; Mościcka, Paulina; Jedwabiński, Marek; Frankowska- Rutkowska, Małgorzata; Cwajda- Białasik, Justyna (Medical and Biological Sciences, 2014)
Among many types of chronic wounds there is a place for traumatic wounds. The circumstances in which they appeared influence their nature. Traumatic wounds are often very deep and a fight to save the wounded parts of the body such as the upper limb requires medical and nursing actions. Proceedings in accordance with the applicable recommendation of scientific societies guarantee a success in the form of restoration of continuity of the skin. A case of 23 years old- man, whose accident at the workplace caused a deep loss for the dorsum of left hand, is presented in the study. Interdisciplinary and local actions based on the latest recommendations in line with the foundation’s strategy resulted in a T.I.M.E strategy have been applied